Women's Experiences of Decision-making and Beliefs in Relation to Planned Cesarean Section: A Survey Study. Issue 4 (December 2021) - Coates, D.; Donnolley, N.; Thirukumar, P.; Lainchbury, A.; Spear, V.; Henry, A.
Abstract : ( Aust N Z J Obstet Gynaecol . 2021;61:106–115) The decision for planned cesarean delivery (CD) is often based on the preferences and beliefs of the patient or clinician. When decision-making is shared, patient satisfaction improves. The extent to which shared decision-making (SDM) occurs in Australia is unclear. Moreover, no studies have directly compared the preferences and beliefs of women undergoing planned CD at the recommendation of the clinician or at their own request. This study aimed to assess the mode of birth preferences of women in Australia and their experiences with SDM for CD. It also aimed to compare the experiences of SDM depending on whether a woman requested a CD or it was recommended by a clinician.